Preliminary study Asymmetrical cortical vein sign (ACVS) predict neurological and radiological improvement in large and distal vessel occlusion post reperfusion therapy - Abdul Rahim, Ezamin; Kamis, Mohd Fandi Al-Khafiz; Che Othman, Azlin Tasnim (Longe Medikal, 2024)
Purpose To investigate the dynamic changes in ACVS on SWIs in patients who underwent reperfusion therapy and evaluate their association with neurological and radiological improvement Materials and Methods All patients treated for acute ischemic stroke between June 2020 and June 2022, in a single tertiary centre (Hospital Sultan Abdul Aziz Shah) who underwent reperfusion therapy and MRI imaging were retrospectively identified based on clinical and radiology reports. Expected Results This study hypothesizes an improvement in ACVS is expected to correlate with favourable neurological outcomes (MRS at 3 months and NIHSS score) and radiological outcome (DWI / ASPECT scores and Modified Mori score). Conversely, a worsening of ACVS is anticipated to be associated with unfavourable neurological and radiological outcomes. Conclusion Asymmetrical Cortical Vein Signs (ACVS) can serve as a valuable predictor of neurological and radiological outcomes in patients with large and distal vessel occlusion after reperfusion therapy